2019
DOI: 10.1088/1757-899x/632/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

The study on the factors influencing the quality of paint and varnish coating when repairing the car body

Abstract: Absract The article presents the main results of the studies on the factors influencing the quality of paint and varnish coating of the car body while performing the emergency recovery repair. The relevance of scientific observations in the presented work is that the issues connected with the quality assessment of applying and drying of paint and varnish coating of the body are not studied to the full extent. It especially concerns the cars that need recovery repair after road accidents. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…A study of the stability of nanocomposites samples and their components in alkaline media showed that SiO2-TiO2, TiO2-ZrO2, and SiO2-ZrO2 nanocomposites samples in alkaline media are subject to dissolution, and SiO2-TiO2-ZrO2 nanocomposite samples do not Following data analysis, it was found that the developed nanoscale composite protective coating is able to maintain its hydrophobic properties (θ ≥ 90 • ) for more than 150 wash cycles. This indicates that the developed preparation has high potential for industrial use as protective composite coatings [43].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A study of the stability of nanocomposites samples and their components in alkaline media showed that SiO2-TiO2, TiO2-ZrO2, and SiO2-ZrO2 nanocomposites samples in alkaline media are subject to dissolution, and SiO2-TiO2-ZrO2 nanocomposite samples do not Following data analysis, it was found that the developed nanoscale composite protective coating is able to maintain its hydrophobic properties (θ ≥ 90 • ) for more than 150 wash cycles. This indicates that the developed preparation has high potential for industrial use as protective composite coatings [43].…”
Section: Discussionmentioning
confidence: 91%
“…Following data analysis, it was found that the developed nanoscale composite protective coating is able to maintain its hydrophobic properties (θ ≥ 90°) for more than 150 wash cycles. This indicates that the developed preparation has high potential for industrial use as protective composite coatings [43].…”
Section: Practical Approval Of Nanoscale Composite Protective Prepara...mentioning
confidence: 91%
See 1 more Smart Citation
“…Coating defects are a common result of various factors that affect the quality of painting (Haryanto and Ichtiarto, 2019). These factors include humidity levels in the room, temperature during drying, excessive layers of paint and varnish, nozzle application distance, nozzle air pressure, and others (Khasanov, Rassokha and Kabanova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Khasanov et al [34] presented main factors influencing the quality of paint and varnish coating when repairing the car body. The main important factors from point of view of the quality of renovation coating were i.e., pollution of compressed air and varnishes, paints and varnishes application on badly prepared surface as well as the use of inappropriate paints and varnishes or the solvent.…”
Section: Introductionmentioning
confidence: 99%